Homiletikai tűnődések a "Jelenések könyve" 5,1–7 kapcsán - Zsolt GÖRÖZDI (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2021)
Homiletical Reflections on the Book of Revelation 5:1–7. The passage mentioned in the title bears several motifs and style charac-teristics of the apocalyptic literature. One of the many difficulties dealing with the text is that such motifs convey the message (Kerygma) in apocalyptic coded language. Therefore, this study seeks to study the biblical text from the aspect of homiletics. It endeavours to provide some guidepost for preaching and to unfold the messages that are relevant for today’s listeners in the church. It addresses se-veral significant topics such as God’s rule, Christ’s (the Lamb slain) mandate, stepping on the throne, the judgement about the earthly power, and the interp-retation of human history in the light of divine rule.